PERSEPSI DUKUNGAN ORGANISASI DAN LEADER-MEMBER EXCHANGE TERHADAP KEINGINAN PINDAH KERJA - Ratih Widyaningrum; Novita Dian Iva Prestiana; Rony Setiawan (SOUL : Jurnal Pemikiran dan Penelitian Psikologi, 2022)
This study aims to determine the effect between perceptions of organizational support and leader- member exchange on turnover intention for employees. This study uses quantitative methods with research design using correlation research. The subjects in this study were employees of PT. Ronadamar Sejahtera, totaling 60 employees. This study used a scale of perceived organizational support with a Cronbach Alpha reliability value of 0.905, a leader-member exchange scale with a Cronbach Alpha reliability value of 0.878 and a scale of turnover intention with a Cronbach Alpha reliability value of 0.751. The data analysis technique used Spearman Rank Correlation and Simple Linear Regression. This study found that there is a significant negative relationship between perceived organizational support and turnover intention and there is a significant negative relationship between leader-member exchange and turnover intention. Furthermore, there is a significant influence between perceived organizational support and leader-member exchange on turnover intention.